(untitled) (Isagoge - Journal of Humanities and Social Sciences, 2026)
The COVID-19 pandemic caused globally disruptions, greatly impacting higher education students through lockdowns and the transition to online learning. This study analyzed the impact that COVID-19 has had on mental health status (anxiety and perceived stress), changes in teaching and academic performance, individual experiences and coping strategies; as well as students’ views on the support measures introduced since the beginning of the pandemic in Botswana and Mauritius. Quantitative data were collected through an online survey administered to students in both countries, with statistical analysis conducted to examine differences by gender and academic level. The findings revealed that female students reported significantly higher anxiety and stress levels compared to their male counterparts. Similarly, undergraduate students experienced higher levels of anxiety and stress than postgraduate students. Policymakers and higher education institutions can use these insights to develop targeted support strategies for students as part of their preparedness plans for future crises.